Selected aspects of heat pumps environmental analysis - Tuchowski, Wojciech; Pietryga, Diana (Instal, 2024)
In the era of energy transformation, the feasibility of replacing heat sources using fossil fuels with renewable heat sources is being increasingly analyzed. This article presents an energy and environmental analysis of heat pumps. The operating conditions of the heat pump were also determined, in which it will be characterized by a high energy efficiency coefficient COP. The cycle of thermodynamic transformations taking place in the classic Linde cycle was analyzed, taking into account the superheating of vapors and subcooling of the refrigerant liquid. The main factors influencing the COP values of a heat pump operating in the heating mode were determined. An environmental analysis was conducted on two units that used different refrigerants, R 410A and R 32. The components of the TEWI index and their weight for the total value were determined. As the calculations show, the substitution of the refrigerant has little impact on the total emission of carbon dioxide into the atmosphere by the heat pump. According to the analysis, a heat pump with R 32 has only a 9.5% lower TEWI value. However, the difference in the GWP of both factors is approximately 70% in favor of R 32.